1993
DOI: 10.1002/1097-0142(19930615)71:12<4043::aid-cncr2820711239>3.0.co;2-a
|View full text |Cite
|
Sign up to set email alerts
|

Repeated use of granisetron in patients receiving cytostatic agents

Abstract: Background. Granisetron was shown to be a safe and effective antiemetic agent when given with initial cytostatic therapy. This study was undertaken to investigate the efficacy and safety of the continued use of granisetron. Methods. Ninety‐one patients were given 438 cycles of granisetron during subsequent courses of cytostatic treatment. In 56 patients, 40 μg/kg IV was given in 159 cycles, and in 42 patients, 3 mg IV was given in 279 cycles. In patients having breakthrough symptoms, as many as two rescue dose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1995
1995
1999
1999

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…After cyclophosphamide-based chemotherapy dexamethasone alone is effective (Koo and Ang, 1996). In trials evaluating the efficacy of anti-emetic agents during multiple cycles of moderately emetogenic chemotherapy (non-cisplatin -Blijham, 1992;Martin et al, 1992;Soukop et al, 1992;Italian Group for Antiemetic Research, 1995a;Silva et al, 1996; non-cisplatin and cisplatin < 50 mg m -2 -de Wet et al, 1993;Kaizer et al, 1994) several diversities in patient population (Blijham, 1992;Martin et al, 1992;Soukop et al, 1992;de Wet et al, 1993;Kaizer et al, 1994;Italian Group for Antiemetic Research, 1995a;Silva et al, 1996), trial methodology (Blijham, 1992;Martin et al, 1992;Soukop et al, 1992;de Wet et al, 1993;Kaizer et al, 1994;Italian Group for Antiemetic Research, 1995a;Silva et al, 1996), or statistical analyses complicate the interpretation of results. Some authors include all patients in the evaluation of anti-emetic effect during multiple cycles (Martin et al, 1992;Soukop et al, 1992;Italian Group for Antiemetic Research, 1995a;Silva et al, 1996), whereas others include only patients with 'good' anti-emetic response during the first cycle of chemotherapy (de Wet et al, 1993;Kaizer et al, 1994) or only those who requested the same anti-emetic treatment in the following cycles (Blijham, 1992).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…After cyclophosphamide-based chemotherapy dexamethasone alone is effective (Koo and Ang, 1996). In trials evaluating the efficacy of anti-emetic agents during multiple cycles of moderately emetogenic chemotherapy (non-cisplatin -Blijham, 1992;Martin et al, 1992;Soukop et al, 1992;Italian Group for Antiemetic Research, 1995a;Silva et al, 1996; non-cisplatin and cisplatin < 50 mg m -2 -de Wet et al, 1993;Kaizer et al, 1994) several diversities in patient population (Blijham, 1992;Martin et al, 1992;Soukop et al, 1992;de Wet et al, 1993;Kaizer et al, 1994;Italian Group for Antiemetic Research, 1995a;Silva et al, 1996), trial methodology (Blijham, 1992;Martin et al, 1992;Soukop et al, 1992;de Wet et al, 1993;Kaizer et al, 1994;Italian Group for Antiemetic Research, 1995a;Silva et al, 1996), or statistical analyses complicate the interpretation of results. Some authors include all patients in the evaluation of anti-emetic effect during multiple cycles (Martin et al, 1992;Soukop et al, 1992;Italian Group for Antiemetic Research, 1995a;Silva et al, 1996), whereas others include only patients with 'good' anti-emetic response during the first cycle of chemotherapy (de Wet et al, 1993;Kaizer et al, 1994) or only those who requested the same anti-emetic treatment in the following cycles (Blijham, 1992).…”
Section: Discussionmentioning
confidence: 99%
“…Using the Kaplan-Meier method we found that the efficacy of both treatments decreased during multiple cycles, but with the method of conditional probabilities the efficacy increased (Table 2). Some trials have reported sustained efficacy of anti-emetic treatment during multiple cycles of moderately emetogenic chemotherapy (Blijham, 1992;de Wet et al, 1993;Kaizer et al, 1994;Italian Group for Antiemetic Research, 1995a;Silva et al, 1996), but in three of these trials the investigators used the method of conditional probabilities for the calculation (Blijham, 1992;de Wet et al, 1993;Kaizer et al, 1994). In two of the studies the number of patients still at risk decreased to less than 10% in cycles 8 and 10 respectively (Blijham, 1992;de Wet et al, 1993) and in the other three (Kaizer et al, 1994;Italian Group for Antiemetic Research, 1995a;Silva et al, 1996) the efficacy was only evaluated during the first three cycles.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To our knowledge no previous report has shown age differences in delayed nausea or vomiting (Carmichael et al, 1994;du Bois et al, 1992;Gandara et al, 1993;Italian Group for Antiemetic Research, 1994;Kaizer et al, 1994;Lindley et al, 1989;Roila et al, 1991). Interestingly, in more recent studies, the evidence provided for an inverse relationship between age and emesis in the acute phase has not been consistent (de Wet et al, 1993;Heron et al, 1994;Italian Group for Antiemetic Research, 1993;Ruff et al, 1994). This may be related to the introduction of new anti-emetic regimens.…”
Section: Effects On Nauseamentioning
confidence: 90%